DIGITAL MSME DEVELOPMENT IN INDONESIA DURING THE COVID-19 PANDEMIC - Primadona (AKSELERASI: Jurnal Ilmiah Nasional, 2020)
This article will discuss the growth of Micro, Small, and Medium-Sized Enterprises (MSMEs) during the Covid-19 epidemic. The Covid-19 pandemic has brought the majority of economic sectors, particularly MSMEs, to a standstill. The surplus is that the majority of MSME actors are unable to develop, resulting in widespread bankruptcy. This forces MSME business actors to rethink their sales strategies in light of digitization initiatives. The digitization strategy makes use of an intermediary (marketplace) and social media as a marketing tool. Additionally, actors in the digital MSME sector must collaborate with netizens to sell their products and services. Thus, the digital MSME development strategy may serve as a viable option to business players being rescued during the Covid-19 pandemic. This essay employs a literature review approach, expanding on existing material on the emergence of digital SMEs. This paper contends that as a result of the Covid-19 pandemic, the development of digital MSMEs has become a viable alternative to saving and promoting digital business in Indonesia.